Dynamics of forest fires about the types of usage and coverage of the earth in the Amazonian Forest of the state of Maranhão, Brazil - Junior, Raymond Nonato Piedade; Junior, Celso Henrique Leite Silva; Campanharo, Wesley Augusto; Santos, Andre Luis Silva dos; Bezerra , Denilson da Silva (Seven Editora, 2023)
The Amazon in the state of Maranhão has recorded several types of degradation causing several damages to the environment and human health. The objective of this work was to understand the dynamics of the burned areas about the usage of the land and coverage in the period from 2001 to 2016 in Maranhão Amazon region. For this purpose we used the coverage and usage soil datas of MapBiomas Project in burned areas of the Fire_cci Burned product Area (BA) v5.0, of precipitation of the Climate Hazards Group InfraRed Precipitation with Station - CHIRPS, and Temperature MODIS LST data from the Global Climate Model Grid (CMG) version 6 (MOD11C3). The proportion of burned areas by land use and cover and the most critical years was identified, relating the area burned to rainfall and monthly temperature. In the studied period, 818,300 hectares were affected by fire. The biggest areas burned were recorded in 2007, 2012 and 2015. Soils with high proportion of pasture showed increasing burnings, compared to other classes. The months of September to November registered the highest occurrence of burned areas presenting precipitations below 50 mm and the highest temperatures in the period. These results indicate the need for actions to prevent, control and manage the usage of fire in the Maranhão Amazon. DOI:https://doi.org/10.56238/alookdevelopv1-080